2016
DOI: 10.4018/ijmhci.2016040103
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Attention and Aging

Abstract: Errors in interaction with digital devices are typically blamed on human factors such as poor attention. However, the influence of attention upon the quality of human-device interaction is commonly overlooked in product design. Developers rely on feedback through user centred design, but do developers, typically younger adults, understand what an older user means, or experiences, in terms of “attention” and appreciate that fundamental conceptual and experiential differences may exist? The authors examine diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…In the MILO Mobile app, selection takes the form of directly touching one of the items with a finger. In the work reported below, and in our previous collaborative work (Basoudan et al, 2019;Jenkins, Lindsay, Eslambolchilar, Thornton, & Tales, 2016; we have always specified that participants respond with the index finger of their dominate hand. Of course, any other instructions may be given, including the use of another finger, a stylus or even responding with more than one finger.…”
Section: Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…In the MILO Mobile app, selection takes the form of directly touching one of the items with a finger. In the work reported below, and in our previous collaborative work (Basoudan et al, 2019;Jenkins, Lindsay, Eslambolchilar, Thornton, & Tales, 2016; we have always specified that participants respond with the index finger of their dominate hand. Of course, any other instructions may be given, including the use of another finger, a stylus or even responding with more than one finger.…”
Section: Taskmentioning
confidence: 99%
“…we have already begun to use the MILO Mobile app to explore changes in response time patterns as a function of both normal (Basoudan et al, 2019;Jenkins et al, 2016) and abnormal (Jenkins et al, 2019;Richards et al, 2019) aging. Our initial results indicate both that the MILO Mobile app can be effectively used with patient groups, and that measures derived from SRT patterns are sensitive enough to identify clinically relevant individual and group differences.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Getting to grips with these challenges is asking difficult cultural questions, which may be approached differently by different age groups. Therefore, M-learning developers are tasked with results that aid such dilemmas -most of whom are from younger age groups themselves [11], having in mind that many educational applications developed for mobile devices were not designed and developed in a way to encourage young students to use technology to promote optimal development [42].…”
Section: Discussionmentioning
confidence: 99%
“…Human-computer interaction (HCI) focuses on how people approach and conduct their relationship with computers [10]; whereas mobile HCI concerns the intricacies of a person's relationship with a mobile system [11,12]. All the specific dynamics, which are liable to be impacted by cultural factors, may affect how the various systems, services, and mobile applications are applied.…”
Section: Introductionmentioning
confidence: 99%
“…The use of tablet technology such as iPads [Rentz, Dekhtyar, Sherman et al, 2016;Dalmaijer, Van der Stigchel, Nijboer et al, 2015;Georgsson & Staggers, 2016;Zapata, Fernández-Alemán, Idri, & Toval, 2015] [Barnett, Blackwell, Sahakian, & Robbins, 2016;Juncos-Rabadan, Pereiro, Faucal et al, 2014;Junkkila, Oja, Laine, & Karrasch, 2012] and a series of studies have indicated that both younger and older adults are comfortable in using this mode of technology i.e. the use of touch screens [Jenkins, Lindsay, Eslambolchilar et al, 2016;Collerton et al, 2007] and are motivated to perform well when using an iPad [Cox, Cains, Shah & Carroll, 2012;Green & Bavelier, 2006;Yee, 2006].…”
Section: Ipad Testingmentioning
confidence: 99%